2000
DOI: 10.1254/jjp.82.287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of YM158, a Dual Lipid Mediator Antagonist, on Immediate and Late Asthmatic Responses, and on Airway Hyper-responsiveness in Guinea Pigs

Abstract: The effects of lipid mediator antagonists: the LTD4-receptor antagonist pranlukast, the TXA2-receptor antagonist seratrodast, and the novel dual LTD4- and TXA2-receptor antagonist YM158 (3-[(4-tert-butylthiazol-2-yl)methoxy]-5'-[3-(4-chlorobenzenesu lfonyl) propyl]-2'-(1H-tetrazol-5-ylmethoxy)benzanilide monosodium salt monohydrate) were investigated in animals exhibiting immediate asthmatic response (IAR), late asthmatic response (LAR) and airway hyper-responsiveness (AHR). Antigen-induced LAR and AfR are inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The effects of CysLT 1 antagonists and a TP antagonist on IAR in animal models have been investigated by many groups. Some groups have reported that these antagonists did not inhibit IAR ( Tohda et al , 1997 ; Ihaku et al , 1999 ; Arakida et al , 2000b ; Yamada et al , 2003 ). Others have reported that these antagonists inhibited IAR significantly, but they required larger doses to inhibit IAR than LAR ( Matsumoto et al , 1994 ; Aoki et al , 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CysLT 1 antagonists and a TP antagonist on IAR in animal models have been investigated by many groups. Some groups have reported that these antagonists did not inhibit IAR ( Tohda et al , 1997 ; Ihaku et al , 1999 ; Arakida et al , 2000b ; Yamada et al , 2003 ). Others have reported that these antagonists inhibited IAR significantly, but they required larger doses to inhibit IAR than LAR ( Matsumoto et al , 1994 ; Aoki et al , 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pranlukast inhibited not only the early-phase bronchoconstriction but also several late-phase responses, including late-phase bronchoconstriction, infiltration of inflammatory cells, and airway hyper-responsiveness (Nakagawa et al, 1993;Arakida et al, 2000). These results suggest that inhibition of leukotriene action may cause the inhibition of the late-phase responses as well as the early airway response.…”
Section: Inhibition By Ta-270 Of Leukotriene Production 587mentioning
confidence: 79%
“…[18][19][20] Glycyrrhizin, a triterpenoid saponin contained in a constituent herb of RKS, Glycyrrhizae Radix, selectively inhibits the activities of arachidonate cascade-related emzymes, such as 5LO and PLA 2 . 21,22) Therefore, it is possible that glycyrrhizin contributes to the prevention of hypersensitivity by RKS.…”
Section: Discussionmentioning
confidence: 99%